2020
DOI: 10.3390/microorganisms8020219
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Soil Microbes Alters Interspecific Competitiveness of Epichloë Endophyte-Infected over Endophyte-Free Leymus chinensis

Abstract: Epichloë endophytes may not only affect the growth and resistances of host grasses, but may also affect soil environment including soil microbes. Can Epichloë endophyte-mediated modification of soil microbes affect the competitive ability of host grasses? In this study, we tested whether Epichloë endophytes and soil microbes alter intraspecific competition between Epichloë endophyte-colonized (EI) and endophyte-free (EF) Leymus chinensis and interspecific competition between L. chinensis and Stipa krylovii. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…There is a symbiotic relationship between cool season grasses (subfamily Pooideae) and Epichloë (= Neotyphodium) fungal endophytes, and the tness of these endophytes and their host plants are tightly coupled (Clay and Schardl 2002). Endophyte infection can promote host plant growth (Chen et (Hill et al 1991(Hill et al ,1998Marks and Cheplick 1991), Festuca pratensis (Malinowski et al 1997), Bromus benekenii (Brem and Leuchtmann 2002) and Leymus chinensis (Liu et al 2020). However, a few studies have yielded inconsistent ndings.…”
Section: Symbiotic Microbes Also Affect the Competitive Ability Of Ho...mentioning
confidence: 99%
“…There is a symbiotic relationship between cool season grasses (subfamily Pooideae) and Epichloë (= Neotyphodium) fungal endophytes, and the tness of these endophytes and their host plants are tightly coupled (Clay and Schardl 2002). Endophyte infection can promote host plant growth (Chen et (Hill et al 1991(Hill et al ,1998Marks and Cheplick 1991), Festuca pratensis (Malinowski et al 1997), Bromus benekenii (Brem and Leuchtmann 2002) and Leymus chinensis (Liu et al 2020). However, a few studies have yielded inconsistent ndings.…”
Section: Symbiotic Microbes Also Affect the Competitive Ability Of Ho...mentioning
confidence: 99%
“…At present, the reported research has focused on the interaction between AMF and Epichloë endophytes (Liu et al, 2017;Zhou et al, 2018). Some studies have found that the effects of endophytes on plant growth and competition are regulated by soil microbes (Liu et al, 2020a;Qu et al, 2023). Here, we selected the natural grass Achnatherum sibiricum as the experimental material.…”
Section: Introductionmentioning
confidence: 99%